An Aurora Kinase B–Based Mouse System to Efficiently Identify and Analyze Proliferating Cardiomyocytes - Fu, Wenbin; Liao, Qiao; Li, Liangpeng; Shi, Yu; Zeng, Andi; Zeng, Chunyu; Wang, Wei Eric (Frontiers in Cell and Developmental Biology, 2020)
To identify and analyze the live proliferating cardiomyocytes is crucial for deciphering the mechanisms controlling endogenous cardiac regeneration. Traditional methods confuse cell division with multinucleation in postnatal cardiomyocytes. Recent efforts have achieved significant progress on discerning cytokinesis from only nuclear division. However, those methods were either designed to label post-cytokinesis progeny or challenging to sort the live proliferating cardiomyocytes. In this study, we highlighted an Aurkb-reporter based mouse system with a tdTomato fluorescence labeling. It could efficiently identify proliferating cardiomyocytes in neonates. The analysis of sorting tdTomato+ cardiomyocytes with different ploidy indicated that mononucleated cardiomyocytes might not possess significantly higher proliferating potential than other cardiomyocytes when most cardiomyocytes have become post-mitotic. Moreover, tdTomato+ cardiomyocytes were significantly increased and enriched at injury border zone after apex resection in neonates, while there were no increased tdTomato+ cardiomyocytes after myocardial infarction in adults.